Preparation method of electrified spontaneous heating ceramic container
By adding bacterial cellulose dry powder to the ceramic container and firing at high temperature, a composite material with conductive and heating is formed, which solves the problem of self-heating of ceramic containers that cannot be energized and achieves a solution to provide excellent insulation effect at low voltage.
Patent Information
- Application Number
- CN202310717473.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
Due to the insulation properties of ceramic containers, they cannot achieve resistance heating, and are difficult to turn on electricity and generate self-heating at high temperatures, which cannot meet the insulation needs.
Bacterial cellulose dry powder is added to the ceramic mixed raw materials, and it is converted into carbon fibers by high temperature firing to form a composite material with conductive and heat generation to realize the self-heating of the ceramic container.
Through the addition of bacterial cellulose, the ceramic container can self-heat at low voltage, provide good insulation effect, and maintain the mechanical properties and structural integrity of the product during high-temperature firing.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a ceramic container, in particular to a method for preparing a ceramic container capable of self-heating when powered on. Background Art
[0002] Ceramics are products made from natural silicates such as clay as the main raw materials. Modern ceramics are often made from non-silicate chemical raw materials or synthetic raw materials, such as oxides (aluminum oxide, zirconium oxide, titanium oxide, etc.) and non-oxides (silicon nitride, boron carbide, etc.). Ceramics have many advantages such as excellent insulation, corrosion resistance, high temperature resistance, high hardness, low density, and radiation resistance, and have been widely used in various fields of the national economy. In particular, the containers we use in daily life, such as cups, bowls, plates, dishes, bottles, etc., are often made of ceramics. As for the containers for holding water and food used in daily life, due to the requirements for water and food insulation, ceramic containers that can be powered on and self-heated are obviously needed by the market. The preparation method of ceramic containers is known in the art. It is usually made by mixing and molding the blanks, firing at high temperature, cooling, glazing, and firing again at high temperature.
[0003] Resistance heating is a method of electrically heating materials by using the thermal effect of electric current passing through a resistor. It has many advantages such as controllable and rapid temperature rise. If the material to be heated is used as a conductor in a circuit, the passage of current will also cause the material to heat up. However, since ceramics are insulators, they cannot be used as conductors in a circuit. Therefore, if ceramic products are to be able to achieve resistance heating, it is necessary to prepare ceramic composite materials to enhance their electrical conductivity and heating properties.
[0004] Bacterial cellulose (BC) is a natural cellulose raw material produced by natural bacterial fermentation metabolism. Compared with ordinary cellulose, it has extremely high purity, basically does not contain impurities such as lignin and hemicellulose, and has an ultra-fine three-dimensional spatial network structure, so it has excellent mechanical properties, and its production cost is low, the cycle is short, and it is environmentally friendly. It is a good natural biological raw material. Cellulose fibers will be carbonized into carbon fibers with conductive properties at high temperatures. Summary of the invention
[0005] The invention provides a method for preparing a ceramic container capable of self-heating when powered on, which comprises adding bacterial cellulose dry powder into ceramic mixed raw materials, mixing them evenly, and then firing them together at high temperature.
[0006] There is no special requirement for the source of bacterial cellulose hydrogel. Bacterial cellulose hydrogels prepared by various culture media and various bacterial fiber-producing bacteria can be used, but bacterial cellulose hydrogel products prepared by static fermentation are preferred. Before use, the bacterial cellulose hydrogel is preferably cleaned and purified, and conventional deionized water and weak alkaline solution cleaning and purification can be used.
[0007] The preparation method of the bacterial fiber dry powder in the present invention is not too limited, and various conventional drying methods can be used, but it is preferably prepared by vacuum freeze-drying and crushing the bacterial cellulose hydrogel after quick freezing. This is because the method of quick freezing combined with vacuum freeze drying will not destroy the fine spatial network structure inside the bacterial cellulose, and after high-temperature firing, such a structure can be maintained, which is conducive to obtaining better conductivity and heat generation performance.
[0008] More preferably, the quick freezing is to pre-cool the cleaned and purified bacterial cellulose hydrogel at 0-5°C, then quickly freeze it at a temperature below -18°C, and then perform vacuum freeze-drying.
[0009] In the present invention, the amount of bacterial cellulose dry powder added is 5-30% of the weight of the ceramic mixed raw material, which can be selected according to the electrical conductivity and heating performance, and is preferably 10-20% of the weight of the ceramic mixed raw material.
[0010] The firing described in the present invention is high-temperature firing at 700-1400°C; preferably at 1200°C; nitrogen can also be introduced for protection during firing.
[0011] The container described in the present invention is one of a pot, a cup, a bowl, a plate, a dish and a bottle.
[0012] The ceramic mixed raw material to which bacterial cellulose dry powder is added described in the present invention can be a mixed blank, a mixed glaze or both; there is no special requirement for the specific formula of the mixed blank or the glaze, but the mixed blank preferably includes: 28-35 parts of kaolin, 6-18 parts of feldspar powder, 3-8 parts of quartz, 3-5 parts of bentonite, and 20-35 parts of bone char; the mixed glaze preferably includes: 25-30 parts of quartz, 5-10 parts of kaolin, 6-18 parts of feldspar powder, 2-3 parts of zircon, 1-2 parts of talc, and 2-3 parts of barium carbonate.
[0013] The invention also provides a self-heating ceramic container prepared by the method.
[0014] The beneficial effects of the present invention are: adding bacterial cellulose powder to the mixed blank, high-temperature firing after molding, the bacterial cellulose can be converted into carbon fibers and evenly distributed in the ceramic blank; or adding bacterial cellulose powder to the mixed glaze, after glazing, high-temperature firing, the bacterial cellulose can be converted into carbon fibers and evenly distributed in the ceramic glaze. The carbon fibers converted from bacterial cellulose can maintain the fine mesh structure of the bacterial cellulose itself, and can be combined with ceramic materials to form a composite material with electrical conductivity and heat generation, which can self-heat when powered at a very low human safety voltage, and such a ceramic container can have a good heat preservation effect when holding water and food. Implementation
[0015] In order to better illustrate the present invention, we provide the following specific implementation modes. It should be noted that the following specific implementation modes are only for facilitating the understanding of the technical solutions of the present invention and shall not constitute any limitation to the present invention.
[0016] Example 1: Preparation of bacterial cellulose powder by hot air drying and crushing The bacterial cellulose hydrogel prepared by static shallow tray fermentation (coconut water culture medium, xylacetobacter xylinum, fermented at 28°C for 7 days) was purified by repeated washing with weak alkaline solution and deionization, dried with hot air at 45°C, and then pulverized through a 100-mesh sieve to obtain bacterial cellulose dry powder.
[0017] Example 2: Preparation of bacterial cellulose powder by vacuum freeze drying and pulverization The bacterial cellulose hydrogel prepared by static shallow tray fermentation (coconut water culture medium, xylacetobacter xylinum, fermented at 28°C for 7 days) was purified by repeated washing with weak alkaline solution and deionization, precooled at 5°C for 2h, then quick-frozen at -18°C for 10h, taken out and vacuum freeze-dried (-35°C, 0.6mbar) to constant weight, and then crushed through a 100-mesh sieve to obtain bacterial cellulose dry powder.
[0018] Example 3: Preparation of embryo self-heating ceramic disk Take 30 parts of kaolin, 15 parts of feldspar powder, 5 parts of quartz, 3 parts of bentonite, and 26 parts of bone char, add 28 parts of bacterial cellulose dry powder prepared in Example 1, stir and mix evenly, then slowly add an appropriate amount of deionized water, continue stirring to form a ceramic blank, prepare it into a plate shape, send it into a kiln, and sinter it at a high temperature of 900°C (heating rate of 10°C / min, firing for 8h), during which N2 protection is introduced, and after completion, cool it to obtain a self-heating ceramic plate when the embryo is energized.
[0019] Example 4: Preparation of a glaze self-heating ceramic disk Take 30 parts of kaolin, 15 parts of feldspar powder, 5 parts of quartz, 3 parts of bentonite, and 26 parts of bone char, mix them, slowly add an appropriate amount of deionized water, and continue to stir to form a ceramic blank. After preparing it into a plate shape, send it into a kiln and sinter it at 900°C at a high temperature (heating rate of 10°C / min, firing for 8h), during which N2 protection is introduced, and then cool it after completion; then take 28 parts of quartz, 9 parts of kaolin, 15 parts of feldspar powder, 3 parts of zircon, 2 parts of talc, and 3 parts of barium carbonate, mix them, add 15 parts of bacterial cellulose dry powder prepared in Example 2, stir and mix evenly, slowly add an appropriate amount of deionized water, continue to stir to form a ceramic glaze, brush the cooled blank with glaze, and then put it into the kiln and fire it again at 1300°C (heating rate of 15°C / min, firing for 2h), during which N2 protection is introduced, and after completion, cool it to obtain a glaze self-heating ceramic plate.
[0020] Example 5: Preparation of a self-heating ceramic cup (heating the embryo and glaze at the same time) Take 32 parts of kaolin, 12 parts of feldspar powder, 6 parts of quartz, 4 parts of bentonite, and 28 parts of bone char, mix them, add 18 parts of bacterial cellulose powder prepared in Example 2, stir and mix evenly, slowly add an appropriate amount of deionized water, continue stirring to form a ceramic blank, prepare it into a plate shape, send it into a kiln, and sinter it at 900°C at a high temperature (heating rate of 10°C / min, firing for 8h), pass N2 protection during sintering, and cool it after completion; then take 26 parts of quartz, 8 parts of kaolin, 12 parts of feldspar powder, 3 parts of zircon, 1 part of talc, and 2 parts of barium carbonate, mix them, add 18 parts of bacterial cellulose powder prepared in Example 2, stir and mix evenly, slowly add an appropriate amount of deionized water to form a ceramic glaze, brush the cooled blank with glaze, and then enter the kiln and fire it again at 1250°C (heating rate of 15°C / min, firing for 2h), pass N2 protection during the period, and cool it after completion to obtain an energized self-heating ceramic cup.
[0021] Experimental Example 1: Experiment on physical properties and electrical performance of ceramic materials 1) Preparation of comparative examples: Prepare the following comparative examples Comparative Example 3: Take 30 parts of kaolin, 15 parts of feldspar powder, 5 parts of quartz, 3 parts of bentonite, and 26 parts of bone char, mix them, stir them evenly, then slowly add an appropriate amount of deionized water and continue stirring to form a ceramic blank. After preparing it into a plate shape, send it into a kiln and sinter it at a high temperature of 900°C (heating rate of 10°C / min, firing for 8h). During this period, N2 protection is introduced. After completion, cool it to obtain a ceramic plate without adding bacterial cellulose dry powder.
[0022] Comparative Example 4: Take 30 parts of kaolin, 15 parts of feldspar powder, 5 parts of quartz, 3 parts of bentonite, and 26 parts of bone char, slowly add an appropriate amount of deionized water, and continue to stir to form a ceramic blank. After preparing it into a plate shape, send it into a kiln and sinter it at 900°C (heating rate of 10°C / min, firing for 8h), pass N2 protection during the period, and cool it after completion; then take 28 parts of quartz, 9 parts of kaolin, 15 parts of feldspar powder, 3 parts of zircon, 2 parts of talc, and 3 parts of barium carbonate, mix them, stir and mix them evenly, slowly add an appropriate amount of deionized water, and continue to stir to form a ceramic glaze, brush the glaze on the cooled blank, and then put it into the kiln and fire it again at 1300°C (heating rate of 15°C / min, firing for 2h), pass N2 protection during the period, and cool it after completion to obtain a glazed ceramic plate without adding bacterial cellulose dry powder.
[0023] Comparative Example 5: Take 32 parts of kaolin, 12 parts of feldspar powder, 6 parts of quartz, 4 parts of bentonite, and 28 parts of bone char, mix them, stir and mix them evenly, slowly add an appropriate amount of deionized water, and continue stirring to form a ceramic blank. After preparing it into a plate shape, send it into a kiln and sinter it at 900°C (heating rate of 10°C / min, firing for 8h). During the sintering, N2 protection is introduced, and then cooled after completion; then take 26 parts of quartz, 8 parts of kaolin, 12 parts of feldspar powder, 3 parts of zircon, 1 part of talc, and 2 parts of barium carbonate. Mix them, stir and mix them evenly, slowly add an appropriate amount of deionized water to form a ceramic glaze, brush the glaze on the cooled blank, and then put it into the kiln and fire it again at 1250°C (heating rate of 15°C / min, firing for 2h). During the period, N2 protection is introduced, and after completion, cooling is performed to obtain a ceramic cup without adding bacterial fiber dry powder.
[0024] 2) Determination of the effect of bacterial cellulose on the physical and chemical properties of ceramic materials by boiling method Preparation of experimental samples: The products in Example 3-5 and Comparative Example 3-5 were broken into pieces, and sample ceramic pieces with a smooth appearance and no obvious defects and cracks were selected, and cut into small discs with a diameter of about 5 cm using a cutting machine for later use.
[0025] Measure the dry weight m1: clean each small disc with an ultrasonic cleaner for 10 minutes, wipe it dry, and dry it in a vacuum drying oven at 110°C to constant weight. Weigh the dry weight m1 to an accuracy of 0.01g, measure three times, and take the average value; Measure the floating weight m2: Put each small disc into boiling water and boil for 2 hours to make it fully saturated. After cooling to room temperature, weigh the mass of the sample in water, which is the floating weight m2, accurate to 0.01g. Measure three times and take the average value; Measure the wet weight m3: Take out the small disc, wipe the sample surface with a wet cloth, weigh the wet weight m3 to an accuracy of 0.01g, measure three times and take the average value; Calculate the volume density of the sample: according to the following formula:
[0026] Calculate the apparent density of the sample: according to the following formula:
[0027] Calculate the porosity of the sample: according to the following formula:
[0028] The measurement and calculation results are shown in the following table:
[0029] From the experimental results, it can be seen that after adding bacterial cellulose dry powder, the density of the composite ceramic product is significantly reduced and the porosity is improved, but it has no significant effect on the quality of the ceramic product.
[0030] 3) Effect of bacterial cellulose on the electrothermal properties of ceramics Preparation of experimental samples: The products in Example 3-5 and Comparative Example 3-5 were broken into pieces, and sample ceramic pieces with a smooth appearance and no obvious defects and cracks were selected, and cut into small discs with a diameter of about 5 cm using a cutting machine for later use.
[0031] i) Resistance experiment: Connect a 6V stable voltage to both ends of the composite ceramic disc, measure the resistance value at different times, and record it every 3 minutes. The results are shown in the table below:
[0032] From the above experimental results, it can be seen that in the initial stage after power-on, the resistance of the composite ceramic disc is significantly reduced, which may be due to the effect of the current breaking through the insulating layer. As the power-on time increases, the resistance of the composite ceramic material stabilizes at about 1.30. Since the bacterial cellulose powder directly dried by hot air is added in Example 3, its network structure may be destroyed during drying, and the fibers are prone to overlap and entanglement, making its resistance value relatively higher. Comparative Examples 3-5 without adding bacterial cellulose are insulators.
[0033] II) Temperature rise experiment: Connect a 6V stable voltage to both ends of the composite ceramic disc, measure the temperature value at different times, and record it every 5 minutes. The results are shown in the following table:
[0034] From the above experimental results, it can be seen that in the initial stage after power-on, the composite ceramic disc begins to heat up slowly, and the heating speed accelerates after 15 minutes, and the temperature stabilizes to about 60 degrees after 25 minutes. Among them, the temperature rises slowly in Example 4, and the temperature is slightly lower, which should be because no bacterial cellulose is added to the blank, and it only relies on the glaze to heat up, and then conducts the heat to the entire ceramic material. The samples of Comparative Examples 3-5 without adding bacterial cellulose cannot heat up.
[0035] In summary, after the bacterial cellulose dry powder is added, it is carbonized to form carbon fibers during the ceramic firing process, which can give the ceramic product electrothermal properties without affecting the quality of the ceramic product and can provide excellent thermal effects at low voltage.
[0036] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field should all fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a self-heating ceramic container when electricity is supplied, Features: Before high-temperature firing, the bacterial cellulose dry powder is added to the ceramic mixed raw materials and mixed evenly, and then fired at high temperature.
2. The method for preparing the self-heating ceramic container according to claim 1, Features: The bacterial cellulose dry powder is prepared by quick-freezing the bacterial cellulose hydrogel, vacuum freeze-drying and pulverizing it.
3. The method for preparing the self-heating ceramic container when powered on according to claim 2, Features: The quick freezing is to pre-cool the cleaned and purified bacterial cellulose hydrogel at 0-5°C and then quickly freeze it at a temperature below -18°C.
4. A method for preparing a self-heating ceramic container according to any one of claims 1 to 3, Features: The amount of bacterial cellulose dry powder added is 15-45% by weight of the ceramic mixed raw material, preferably 30-35%.
5. The method for preparing the self-heating ceramic container when powered on according to claim 4, Features: The firing is carried out at a high temperature of 700-1400°C; nitrogen is introduced during the firing for protection.
6. The method for preparing the self-heating ceramic container when powered on according to claim 5, Features: The firing temperature is 1200°C.
7. The method for preparing the self-heating ceramic container when powered on according to claim 5, Features: The container is one of a pot, a cup, a bowl, a plate, a dish and a bottle.
8. The method for preparing the self-heating ceramic container when powered on according to claim 1, Features: The ceramic mixed raw material is a mixed blank and / or a mixed glaze.
9. The method for preparing the self-heating ceramic container when powered on according to claim 8, Features: The mixed blank comprises: 28-35 parts of kaolin, 6-18 parts of feldspar powder, 3-8 parts of quartz, 3-5 parts of bentonite, and 20-35 parts of bone char; the mixed glaze comprises: 25-30 parts of quartz, 5-10 parts of kaolin, 6-18 parts of feldspar powder, 2-3 parts of zircon, 1-2 parts of talc, and 2-3 parts of barium carbonate.
10. A self-heating ceramic container prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of bacterial cellulose based carbon nanofibers
CN103820883A
Ceramic electric kettle and preparation method thereof
CN107540358A
Method for manufacturing electrothermal functional ceramic through vacuumizing method, product and application method
CN110436903A
Fiber material and method for producing fiber material, and composite material and method for producing composite material
JP2018111768A
